MEMBANGKITKAN MOTIVASI BELAJAR PESERTA DIDIK DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM PADA MATERI MENGENAL SURAH AL-INSYIRAH DI SEKOLAH DASAR - Siti Naima Masri; Umar Sadjim (PEDAGOGIK, 2021)
The purpose of this study is to generate learning motivation among students in learning Islamic religious education in elementary schools using the material about knowing Surah Al-Insyirah. The type of research used is library research.The data collection technique used in this study was to examine various sources and references related to the research variables, which came from textbooks and journals on students' learning motivation in learning Islamic education, which discusses surah Al-insyirah. Reference sources that have been obtained are then reviewed and analyzed to obtain data that is in accordance with the research focus. As for library research, the main data sources consist of primary data sources and secondary data sources. Secondary data is data obtained from sources that discuss less according to the research focus, while primary data is a source that discusses a lot of issues related to the research focus. The data analysis technique is using Miles & Huberman data analysis with data collection, data verification, and drawing conclusions.Based on the results of studies and analysis of sources both references and journals, it shows that teachers can generate students' learning motivation in learning Islamic education with material about knowing Surah Al-Insyirah in Elementary Schools by using various methods and various learning media. For coherence or linkage of indicators of student learning motivation through learning Islamic Religious Education about knowing Surat al-Insyirah, consisting of; (a) knowing the laws of reading, (b) how to read the letter al-Insyirah, (c) knowing the letter al-Insyirah by knowing its asbaabun nuzul briefly, (d) practicing writing the letter word for word, (e) practicing memorizing it, (f) exercises to match word fragments to prepare for memorization, (g) and calligraphy writing (art) which is carried out in groups,